Oxford Mini School French Dictionary - Grundy, Valerie (Oxford University Press, 2004)
This new edition has been fully expanded to include over 800 new headwords with particular attention paid to money, computing and word processing terminology, sport and leisure, and environmental terms and professions. Updated for 2004 with over 800 new entries covering: money (with value of euro compared with old currency and, colloquial survival of 'centime' in the new currency system); computing and word processing (smart card, telephone card, text messaging, gigabyte); environmental terms (ozone layer, oil slick), professions (astronomer, graphic designer etc), sport and leisure (hiking, fitness, lifeguard), even includes SARS. Its features include: new design to increase clarity of layout, 2 colour with virtual alphabet tabs; perfect for individual use as a quick reference tool or extended classroom work; links to NLS modern languages curriculum - all syllabus words included; includes French in North America and Caribbean geographical terms; and colour headwords, phrases, verb tables and virtual alphabet tabs. Nicholas Rollin is an experienced editor of bilingual dictionaries